The Adoption of Genetically Modified Crops in Africa: the Public’s Current Perception, the Regulatory Obstacles, and Ethical Challenges - Gideon Sadikiel Mmbando (GM Crops & Food, 2024)
Genetically modified (GM) crops are the most important agricultural commodities that can improve the yield of African smallholder farmers. The intricate circumstances surrounding the introduction of GM agriculture in Africa, however, underscore the importance of comprehending the moral conundrums, regulatory environments, and public sentiment that exist today. This review examines the current situation surrounding the use of GM crops in Africa, focusing on moral conundrums, regulatory frameworks, and public opinion. Only eleven of the fifty-four African countries currently cultivate GM crops due to the wide range of opinions resulting from the disparities in cultural, socioeconomic, and environmental factors. This review proposed that addressing public concerns, harmonizing regulations, and upholding ethical standards will improve the adoption of GM crops in Africa. This study offers ways to enhance the acceptability of GM crops for boosting nutrition and food security globally.